2023
DOI: 10.33594/000000661
|View full text |Cite
|
Sign up to set email alerts
|

Trimethylamine N-Oxide (TMAO): a Unique Counteracting Osmolyte?

Paul H. Yancey

Abstract: Cells of many organisms facing osmotic shrinkage or swelling undergo homeostatic volume regulation using osmolytes—inorganic ions (Na+, K+, Cl-) in transient disturbances, but special organic osmolytes in long-term disturbances. Neutral amino acids, methylamines and polyols are key examples. Widely termed 'compatible' cosolutes/cosolvents, they—unlike inorganic ions—do not perturb membrane potential nor (supposedly) macromolecules. Indeed, most enhance protein stability in part through preferential exclusion; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 143 publications
0
5
0
Order By: Relevance
“…In normal circumstances, TMAO plays a crucial role in regulating fluid balance, stabilizing protective functions and aiding in preserving the integrity of cells [ 44 ]. However, TMAO has been identified as an inflammatory and proatherogenic molecule when present at a value over the physiologic range and impairs angiogenesis, repressing the CXCR4 axis [ 45 , 46 , 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In normal circumstances, TMAO plays a crucial role in regulating fluid balance, stabilizing protective functions and aiding in preserving the integrity of cells [ 44 ]. However, TMAO has been identified as an inflammatory and proatherogenic molecule when present at a value over the physiologic range and impairs angiogenesis, repressing the CXCR4 axis [ 45 , 46 , 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Methylamines such as betaine and TMAO are present in cells in many animals, including mammals. 7,17 In cartilaginous fish such as sharks, TMAO acts as a stabilizer. Several studies on protein conformational stability and functional activity have demonstrated that when urea destabilizes proteins and reduces their function, half to equivalent amounts of TMAO counteract the effect of urea.…”
mentioning
confidence: 99%
“…Various molecules, such as cosolvents and osmolytes, are present in cells to regulate cell volume, structural stability and function of biomolecules, and molecular crowding effects. Numerous studies have investigated the impact of crowder molecules, including polysaccharides, monosaccharides, glycerol, and osmolytes such as trimethylamine N -oxide (TMAO) and urea with respect to protein denaturation temperature and pressure. For example, sucrose, sorbitol, glycerol, and TMAO increase denaturation temperatures by 2–4 °C/M and denaturation pressures by ∼2 kbar/M . One mechanism underlying protein stabilization is the excluded volume effect.…”
mentioning
confidence: 99%
See 2 more Smart Citations